Decision-Making Skills Among Members of The Iraqi Kurdistan Parliament (Raparin Journal of Humanities (RJH), 2025)
The aim of the current research is to identify the level of decision-making skills among members of the Iraqi Kurdistan Parliament, and the significance of the differences in them according to demographic variables (gender, age, nationality, educational level, years of service in Parliament). The research relied on the descriptive survey method, and the sample consisted of (95) male and female members selected from the members of the fifth session of the Iraqi Kurdistan Parliament, to whom the decision-making skills scale that had been prepared was applied, which in its final form consisted of (31) items. Its validity and reliability were verified. After analyzing the data using SPSS, the results showed that the level of decision-making skills among members of the Iraqi Kurdistan Parliament in general is high, and it was found that there are no statistically significant differences in decision-making skills attributed to the variables: gender, age, nationality, academic level, and years of service in Parliament. In light of the results included a number of recommendations for stakeholders and some suggestions for future researchers.